Dél-dunántúli régió helyzete, fejlesztési lehetősége - Buday-Sántha, Attila (Közép-Európai Közlemények, 2013)
The South Transdanubian Region is a region in a critical condition which economic performance is continuously lagging behind the national average, and which still has not found its path after the social-economic transition of Hungary. The economic performance and the employment capacity of the former industry could not be fully substituted by the new industries which settled down in the region on the basis of the collapsed one. The situation was worsening by the deterioration of the performance of the agriculture. On the other hand, the reduction in the performance of the productive sectors could have been counterbalanced neither by the tourism, nor by the development of the service sector. While the capital attraction ability of the region is extremely weak (only 1.1% of the foreign direct investment has flown into the region), thus the development of the region is determined by the fact that to what extent the region’s own resources can be exploited and how much financial transfers can be obtained by the region from the central government. Therefore, the further deterioration of the region can be refrained on the one hand with a regional development policy which concentrates on the elimination and conscious counterbalance of the regional disadvantages, on the other hand, with a future-oriented development policy harmonized among the counties and the economic organizations of the region.